2017
DOI: 10.3389/fpsyt.2017.00100
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation Interventions to Promote Recovery from Schizophrenia: A Systematic Review

Abstract: Only one out of seven patients recovers after a first episode of psychosis despite psychiatric care. Rehabilitation interventions have been developed to improve functional outcomes and to promote recovery. We conducted a systematic review of the effectiveness of the main psychiatric rehabilitation interventions following a search of the electronic databases Pubmed, ScienceDirect, and Google Scholar using combinations of terms relating to cognitive remediation, psychoeducation, cognitive-behavioral therapies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
107
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(119 citation statements)
references
References 100 publications
(192 reference statements)
3
107
0
4
Order By: Relevance
“…[5][6][7] In recent years, much has been written about recovery from psychosis. [8][9][10][11][12][13][14][15][16][17][18] There has been a growing awareness towards the central role and influence human relationships have in the recovery process. [12][13][14][15][16][17][18] Several studies have focused on the importance of user involvement 13,14,[18][19][20] and staff attitudes, 16,[21][22][23][24][25][26][27] but, interestingly, very little attention has been paid to how leading textbooks in the mental health field describe and present people having psychosis and how psychosis as such is communicated to students and the professionals.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In recent years, much has been written about recovery from psychosis. [8][9][10][11][12][13][14][15][16][17][18] There has been a growing awareness towards the central role and influence human relationships have in the recovery process. [12][13][14][15][16][17][18] Several studies have focused on the importance of user involvement 13,14,[18][19][20] and staff attitudes, 16,[21][22][23][24][25][26][27] but, interestingly, very little attention has been paid to how leading textbooks in the mental health field describe and present people having psychosis and how psychosis as such is communicated to students and the professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The Turkish validity and reliability study of the 30-item scale was performed by Voltan. 33 The 3, 6,7,8,10,18,20,21,22,25,27,28, and 29th items (13 items) are positive expressions; and the 1,2,4,5,9,11,12,13,14,15,16,17,19,23,24,26, and 30th items (17 items) are negative expressions. Expressions are scored from a range of 1 to 6 and the positive expressions are reversed.…”
Section: Rathus Assertiveness Schedulementioning
confidence: 99%
“…3,4 While drug therapy in schizophrenia targets positive and negative symptoms, disorganized behaviors, mood, and cognitive symptoms; psychosocial interventions including programs such as individual interviews, family education, social skills training, holistic approach group therapies, supportive therapy, and cognitive-behavioral therapies are provided for self-care deficiencies, poor quality of life, interpersonal relationship problems, noncompliance with treatment, dysfunctions, addiction, and signs of disability in social and professional skills. [5][6][7][8][9] It has been reported that psychosocial skills training, which is frequently applied in the rehabilitation of schizophrenia patients, increases quality of life, social functioning levels, self-esteem, communication skills, compliance to treatment levels, and insights of the patients; reduces disability, relapse, and repeated hospitalization; and has positive effects on positive and negative symptoms. [10][11][12][13][14][15] It is also reported that social skills training programs increase interpersonal relationships and assertiveness skills in schizophrenia.…”
mentioning
confidence: 99%
See 2 more Smart Citations